2007
DOI: 10.1083/jcb.200705180
|View full text |Cite
|
Sign up to set email alerts
|

A molecular specificity code for the three mammalian KDEL receptors

Abstract: AC-terminal KDEL-like motif prevents secretion of soluble endoplasmic reticulum (ER)–resident proteins. This motif interacts with KDEL receptors localized in the intermediate compartment and Golgi apparatus. Such binding triggers retrieval back to the ER via a coat protein I–dependent pathway. To date, two human KDEL receptors have been reported. Here, we report the Golgi localization of a third human KDEL receptor. Using a reporter construct system from a screen of 152 variants, we identified 35 KDEL-like var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
211
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(229 citation statements)
references
References 29 publications
13
211
1
2
Order By: Relevance
“…AGR2 was initially assumed to be a secreted protein, based on the presence of a predicted signal peptide at the amino terminus (8). However, more recent analysis identified an ER localization signal and thioredoxin-like domain sequences, suggesting that AGR2 is a PDI (3,12). We found that AGR2 is localized to the ER in intestinal epithelial cells and did not detect AGR2 in secretory granules or in the intestinal lumen.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…AGR2 was initially assumed to be a secreted protein, based on the presence of a predicted signal peptide at the amino terminus (8). However, more recent analysis identified an ER localization signal and thioredoxin-like domain sequences, suggesting that AGR2 is a PDI (3,12). We found that AGR2 is localized to the ER in intestinal epithelial cells and did not detect AGR2 in secretory granules or in the intestinal lumen.…”
Section: Discussionmentioning
confidence: 60%
“…AGR2 was originally presumed to be another secreted protein produced by goblet cells (8). However, AGR2 has a carboxyl-terminal KTEL sequence, and a recent analysis indicated that this sequence was recognized by ER retention receptors and served to localize AGR2 predominantly to the ER of transfected cells (12). In addition, AGR2 has a single thioredoxin-like domain with a CXXS motif (3).…”
mentioning
confidence: 99%
“…6A, Upper Right). The increased ER targeting efficiency of H8-KDEL is likely through the retrograde transport system from Golgi to ER via the KDEL receptors (30)(31)(32). In vivo, the H8-KDEL peptide caused mislocalization of rhodopsin to the inner segment and perinuclear ER region (yellow and white arrows, respectively, in Fig.…”
Section: Disruption By Helix Peptides Of R-and S-opsin Trafficking Inmentioning
confidence: 99%
“…Although a C-terminal KDEL sequence is the canonical retention signal, the KDELRs also have some affinity for similar sequences. An in vitro screen examining the ability of short peptides to interact with the KDELRs revealed 40 -80% percent binding of the RTDL sequence compared with the canonical KDEL sequence (16). It is possible that differences in affinity for the KDELR are important for MANF secretion, and a competition model for ER retention could explain the rapid secretion of MANF in response to ER stress.…”
mentioning
confidence: 99%